Revolutionizing Business: The Role of AI in Driving Industry 4.0 - Nabiel Syarof Azzaky; Atikah Salimah; Clarita Risma Saputri (TechComp Innovations: Journal of Computer Science and Technology, 2024)
The urgency of this research lies in understanding the critical role of Artificial Intelligence (AI) in the rapidly evolving landscape of Industry 4.0. As businesses strive to remain competitive, AI's integration into industrial processes has become essential. The primary aim of this study is to examine how AI drives innovation and efficiency within Industry 4.0. Using a literature review methodology, this research synthesizes findings from existing studies to provide a comprehensive overview of AI's impact on various business sectors, including manufacturing, logistics, and supply chain management. The results reveal that AI significantly enhances operational efficiency, predictive maintenance, and decision-making capabilities. Moreover, the study identifies key challenges in AI implementation, such as data privacy and the need for skilled workforce, while also highlighting the vast opportunities for future advancements. This research underscores the importance of AI in achieving higher levels of customization, quality, and competitiveness, paving the way for sustainable business growth in the digital era